Auditory decision making in mice: - Florian, Steinfeld (2021)
"Forming appropriate decisions based on the state of the outside world is an essential skill animals need to survive. While several tasks to study rodent decision making have been proposed, many aspects of perceptual decision making and their neural correlates remain poorly understood. In this thesis we focused on three separate aspects of auditory decision making in mice, each represented by one of the following chapters.(...)"